Analisis Media Pembelajaran Berbasis Canva terhadap Hasil Belajar Informatika Siswa Kelas X di SMK Wikrama Bogor - Nafla Fatina Zahira; Amiruddin Saleh; Harvia Atika Zahira (Lembaga Pendidikan, Penelitian, dan Pengabdian Kamandanu, 2026)
Canva-based learning media represents a digital innovation increasingly adopted in Vocational High Schools (SMK); however, in-depth studies regarding its impact on informatics learning outcomes from the perspectives of both teachers and students—remain limited. This study aims to analyze the impact of Canva-based learning media on the informatics learning outcomes of Grade X students at SMK Wikrama Bogor. The research employs a descriptive qualitative approach, utilizing semi-structured, in-depth interviews with two informatics teachers and four Grade X students selected via purposive sampling. Data analysis was conducted descriptively and qualitatively, with validity ensured through source triangulation. The study reveals four key findings: First, Canva facilitates the understanding of informatics material through concise and structured visual presentations; second, Canva boosts student motivation and engagement by allowing for creative self-expression; third, Canva improves the efficiency of assignment completion, enabling students to dedicate more cognitive energy to the subject matter itself; and fourth, challenges related to internet connectivity reliance can be mitigated through adaptive teaching strategies. It is concluded that Canva-based learning media positively influences the informatics learning outcomes of Grade X students at SMK Wikrama Bogor, affecting both cognitive and affective domains.